Exact renormalization of massless QED(2) - Casana, R.; Dias, S. A. (World Scientific Publ Co Pte Ltd, 2002)
We perform the exact renormalization of two-dimensional massless gauge theories. Using these exact results we discuss the cluster property and confinement in both the anomalous and chiral Schwinger models.
Keywords: renormalization; two-dimensional gauge theories; confinement